PECULIARITIES AND SIGNIFICANCE OF ORGANIZING INCOME AND EXPENSE ACCOUNTING BASED ON INTERNATIONAL STANDARDS - Egamberdiyeva, Salima Rayimovna; Jo‘rayev, Og‘abek Sherali o‘g‘li; Samadova, Marjona Feruzbek qizi (THE INNOVATION ECONOMY, 2026)
This article presents proposals and recommendations on key areas for improving the accounting and control of income and expenses. In the context of the formation of the digital economy, the effective use of financial indicators is of great importance in the activities of economic entities. The financial result of income and expenses is an important criterion for joint business management, as well as for attracting investors and partners to creditors.